Navigating conflicting phonotactic constraints in bilingual speech perception*. Issue 5 (26th June 2015) - CARLSON, MATTHEW T.; GOLDRICK, MATTHEW; BLASINGAME, MICHAEL; FINK, ANGELA
Abstract : Word-initial /s/-consonant clusters do not occur in Spanish. Confronted with such sequences (e.g., in loanwords), Spanish speakers tend to perceive an illusory initial /e/, 'repairing' the illicit sequence. In two experiments, both conducted in Spanish with Spanish-sounding nonwords, we ask whether knowledge of English, which has no restriction against this sound sequence, weakens this pattern of perceptual repair in fluent Spanish–English bilinguals, and whether the effects of English depend on language dominance. In both identification and discrimination tasks, bilinguals exhibited weaker perceptual repair effects relative to Spanish monolinguals. This was true even for bilinguals dominant in Spanish, though the weakening was more pronounced for English-dominant bilinguals. These results show that conflicting phonotactic systems can jointly influence bilinguals' perceptual repair of the acoustic signal in the more restrictive language, even when it is the bilingual's dominant language, suggesting a degree of integration and mutual influence of knowledge between both their languages.